DA'WAH STRATEGY IN PREVENTING APOSTASY IN CISANTANA VILLAGE, CIGUGUR DISTRICT, KUNINGAN DISTRICT - Muzayyanah Yuliasih; Tri Rahyu (Program Studi Pengembangan Masyarakat Islam STID Mohammad Natsir, 2022)
The purpose of this research is to find formulations and methods of da'wah strategies and management that are effective for the community in warding off solicitations or inducements to change to other religions. The method used in this study is descriptive qualitative, with a field observation approach to the problem to be studied. The results of the study found that an effective way to prevent Christianization in the Cisantana village community, Cigugur sub-district, Kuningan district, can be done in various ways; da'wah bil hall or with concrete actions, such as strengthening the people's economy through empowering the Baitul Maal (collecting zakat infaq, grants, and almsgiving), increasing the quality and quantity of Islamic-based education (Islamic boarding schools and other Islamic religious schools), strengthening Islamic ukhuwah among people.